Workshop Pemanfaatan Microsoft Word untuk Optimalisasi Manajemen Pembuatan Karya Ilmiah bagi Pelajar - Norma Ningsih (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of technology and the increasingly rapid exchange of information encourages us to continue to improve our abilities so that we can adapt our abilities according to the needs and demands of the times. Making scientific work is a positive and beneficial activity for teenagers both at the school and university levels. This can increase analytical power and develop research in their respective fields. The purpose of this Community Service activity is to help teenagers, especially students, to be able to take advantage of the Microsoft Word application in making a scientific document so that it is more efficient and in accordance with the rules of writing scientific papers. The preparation of this document uses Microsoft word according to the rules of writing scientific papers which contain several materials including paragraph formats, object management to making bibliography. Through this Microsoft word workshop students can use it to create scientific papers, assignments, reports to journal articles.Keywords: Workshop, Scientific work, Microsoft word